The Effect of Murottal and Dzikir Therapy on Stress Levels of Cervical Cancer Patients in the First Chemotherapy Program - Tiara Septiana; Diyanah Syolihan Rinjani Putri; Setiyawan Setiyawan (GLOBAL HEALTH SCIENCE GROUP, 2025)
Cervical cancer patients stage IIIB receive their first chemotherapy treatment. One of the effects of chemotherapy is that it can cause stress. Stress, as a psychological effect, worsens many diseases and pathological conditions and weakens the immune system. This can reduce the cytotoxic activity of T lymphocyte cells and thus increase cell proliferation. The combination of murottal and dhikr therapy can be considered a comprehensive approach to dealing with stress. After listening to murottal, a person may feel more connected to the verses of the Qur'an. Dhikr therapy, as a form of repetition and reflection on the greatness of Allah, can be the next step in strengthening spiritual bonds and relieving stress. Purpose: This study aims to determine the stress level of cervical cancer patients in the first chemotherapy program with murottal and dhikr therapy at Dr. Moewardi Hospital. Method: This type of research is quantitative research with the research design used is Quasy Experiment one group pre test-post test design. The total population of the study was 52 patients. The sample in this study was cervical cancer patients at Dr. Moewardi Hospital, a total of 52 patients using the total sampling technique. This study was conducted in the tulip rooms 4 and 5 of Dr. Moewardi Hospital. Moewardi. on March 25, 2024 – May 13, 2024. Stress assessment indicators using the Perceived Stress Scale (PSS-10). Murottal therapy intervention with a duration of 17 minutes 40 seconds and dhikr with a duration of 2 minutes. Result: Data analysis using parametric testing in the form of a Paired T-Test with a confidence level of 95%. The pretest stress level of murottal and dhikr administration with a mean of 17.17 and a posttest stress level of 13.77. Conclusions: The results of the Paired T-Test were significant at 0.000 <0.05 indicating that there was an effect of murottal and dhikr therapy after the first chemotherapy.